REKONSILIASI TRADISI MUSLIM DAN SAINS MODERN Telaah atas Buku Islam’s Quantum Question Karya Nidhal Guessoum - Muhammad Solikhudin (IAIN Tulungagung, 2016)
The religion and science debate seem unrelenting. Science and technology are key element in the progress of human civilization towards the established of a knowledge-based society. But, science without religion is lame; religion without science is blind. The human life need direction and guidance. Science does notconflict with Islam, because the philosophy and theoretical foundations as well as the formula used by science turned out to be derived from the Koran and Hadith. Koran and Hadith are the main principle for developing the science and application of science through technology. In this paper the author triesto discuss the study of religion and science in which the author examines the book by Nidhal Guessoum, then analyzed with a phenomenological approach.Keywords: Religion, Science, Phenomenology.